Esterification of fatty acids with glycerol over Fe-Zn double-metal cyanide catalyst - Kotwal, Mehejabeen; Deshpande, Suvarna S.; Srinivas, D. (Catalysis Communications, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complex exhibits high catalytic activity for esterification of fatty acids (FA) with glycerol. DMC catalysts with varying acidities were prepared by synthesizing the material at four different temperatures (10, 25, 50 and 80 degrees C). The catalyst prepared at 50 degrees C exhibited highest catalytic activity. Catalytic activity of DMC was influenced by both acidity and surface area. Complete conversion of FA was achieved at 140-200 degrees C under atmospheric pressure. Chain length of FA was found to influence the rate of reaction and product selectivity. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid-catalyzed reaction; Double-metal cyanide (DMC); Esterification of fatty acid; Fatty acid glycerides; solid acid catalyst

Three-dimensional, mesoporous titanosilicates as catalysts for producing biodiesel and biolubricants - Kotwal, Mehejabeen; Kumar, Anuj; Darbha, Srinivas (Journal of Molecular Catalysis A-Chemical, 2013)
The application of three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16, as reusable solid acid catalysts for producing biodiesel and biolubricants is reported for the first time. Biodiesel was prepared by esterification of oleic acid with monohydric methanol and biolubricants by esterification with polyhydric alcohols (glycerol, trimethylolpropane, neopentyl glycol and pentaerythritol). High catalytic activity of these catalysts is attributed to the presence of dispersed Lewis acidic Ti sites and mesoporosity in the structure. Biodiesel yields as high as 90 mol% were obtained at 443 K. Surface hydrophobicity of the catalyst has also a predominant role, especially, in reactions involving polyhydric alcohols. In those reactions, Ti-SBA-16 showed higher catalytic activity than Ti-SBA-12. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; Esterification of fatty acid; Lubricant basestocks; mesoporous materials; Ti-SBA-12; Ti-SBA-16; Titanosilicates

Zirconium phenyl phosphonate phosphite as a highly active, reusable, solid acid catalyst for producing fatty acid polyol esters - Varhadi, Poonam; Kotwal, Mehejabeen; Srinivas, D. (Applied Catalysis A-General, 2013)
The application of zirconium phenyl phosphonate phosphite (ZrPP) as a solid acid catalyst for producing polyol esters by esterification of glycerol or trimethylolpropane with a fatty acid (C-8-C-18.1) is reported for the first time. ZrPP exhibits high catalytic activity and in particular, (di + tri) esters selectivity (92.3 mol%). These esters of polyols are known for their application as biolubricants. The catalyst prepared using phosphorous acid to phenyl phosphonic acid molar ratio of 3:1 was found superior. The influence of process parameters on activity and selectivity of the catalyst was investigated. ZrPP was reusable in at least three recycling experiments. Hydrophobicity due to exposed phenyl groups on the surface is the possible cause for superior esterification activity of this novel, solid catalyst. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biolubricants; Esterification of fatty acid; Fatty acid glycerides; Hydrophobic solid acid catalyst; Polyol esters; Zirconium phenyl phosphonate phosphite